2006
DOI: 10.1007/s00268-005-0398-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Familial Non‐Medullary Thyroid Cancer Adversely Affect Survival?

Abstract: Our results suggest that FNMTC may be more aggressive than sporadic thyroid cancer, particularly in families with 3 or more affected members. However, when recognized and treated appropriately, it does not significantly shorten the overall life expectancy of the affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 30 publications
(52 reference statements)
5
78
2
2
Order By: Relevance
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussioncontrasting
confidence: 37%
“…In a retrospective matched-case control study of FNMTC, the majority being PTCs, Maxwell et al (24) reported that familial cases tend to have, but not significantly, improved DFS and disease-specific survival. In a classical study (34), based on probability calculation analysis, Charkes pointed out that up to 60% of familial PTCs diagnosed in families with only two affected members might, actually, represent a fortuitous aggregation of sporadic cases, suggesting that the disease may be more accurately diagnosed in families with three or more affected members (17,21). This fact could, therefore, also contribute to misestimate the aggressiveness of familial PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observou que após tratamento, o carcinoma não afetou significativamente a sobrevida de pacientes quando comparados com membros de sua família não acometidos ou com a população geral dos Estados Unidos. Contudo, aqueles que faziam parte de famílias com três ou mais membros afetados apresentavam uma sobrevida mais curta quando comparados com famílias com somente dois membros acometidos (14).…”
Section: Característicasunclassified
“…Unfortunately, prophylactic thyroidectomy, directed by genetic testing, currently can not be recommended to remove the thyroid gland in patients who are genetically predisposed to developing FPTC. (48) reported that patients with three or more members with FPTC were more likely to die from their thyroid cancer than those with just two documented patients with thyroid cancer or patients without thyroid cancer. Index cases had a higher death rate than subsequent family members (48).…”
Section: Familial Non-medullary Thyroid Cancermentioning
confidence: 99%